Peranan World Cosplay Summit terhadap Budaya Populer dalam Diplomasi Budaya Jepang pada Tahun 2014 - Amelia, Winda; Argenti, Gili; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research explores the role of the World Cosplay Summit (WCS) as a tool of Japanese cultural diplomacy through popular culture to strengthen Japan's positive image internationally. Using a descriptive qualitative approach, this research utilizes secondary data in the form of literature and documentation related to Japanese cultural diplomacy and the role of popular culture such as cosplay, anime, and manga. The results show that the WCS not only promotes the values of freedom of expression contained in Japanese popular culture, but also creates a platform for the creativity of young people in various countries. The success of this diplomacy is marked by the increasing number of countries participating in the WCS, proving the effectiveness of popular culture as an instrument of Japan's soft power in cultural diplomacy.